Globalization, Labor Market Regulation, and Firm Behavior - Moritz Meyer; Paul Vandenberg (Asian Development Bank (ADB), 2013)
The paper analyzes the link between firm characteristics and labor market regulation in five Asian economies - Bangladesh, Indonesia, Pakistan, the Philippines, and Viet Nam. Labor market policies and labor standards do not only affects workers, but also influence firms' investment and employment decisions. The empirical analysis uses information from enterprise surveys. Empirical results describe systematic differences in the perceived level of labor market regulation. Controlling for a wide set of firm characteristics, the perceived level of labor market regulation is found to vary between firms that participate in global trade as against those supplying the domestic market. The in-country location of a firm is also a significant determinant. The level of labor intensity explains variation in the reported level of labor market regulation between firms. Findings support a better understanding of the types of firms that find labor market regulation to be an obstacle to their operations, and can be used to design targeted policy interventions.
hdl:11540/2080
Keywords: D22; F16; J23; 330; labor market institutions (regulation); trade and labor markets; developing countries